Sub-acute Toxicity in Non-cancerous Tissue and Immune-Related Adverse Events of a Novel Combination Therapy for Cancer - McKelvey, Kelly J.; Hudson, Amanda L.; Prasanna Kumar, Ramyashree; Eade, Thomas; Clarke, Stephen J.; Wheeler, Helen R.; Diakos, Connie I.; Howell, Viive M. (Frontiers in Oncology, 2020)
Brain, lung and colon tissue experience deleterious immune-related adverse events when immune-oncological agents or radiation are administered. However, there is a paucity of information regarding whether the addition of radiation to immuno-oncological regimens exacerbates the tissue inflammatory response. We used a murine model to evaluate sub-acute tissue damage and the systemic immune response in C57Bl/6 mice when administered systemic anti-programmed cell death protein 1 (αPD-1) immunotherapy alone or in combination with stereotactic fractionated 10 gray/5 X-ray radiation to normal brain, lung or colon tissue. The model indicated that combinatorial αPD-1 immunotherapy and radiation may alter normal colon cell proliferation and cerebral blood vasculature, and induce systemic thrombocytopenia, lymphopenia, immune suppression, and altered immune repertoire (including interleukin-1β). Therein our data supports close monitoring of hematological and immune-related adverse events in patients receiving combination therapy.